Pengaruh Fasilitas, Word of Mouth, dan Promosi Media Sosial terhadap Keputusan Generasi Milenial dalam Memilih Tempat Berolahraga di New Raja Gym Banda Aceh - Ariq Alfarisi; Amelia Amelia; Mirza Murni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Advances in information technology have brought about major changes in marketing strategies and consumer behavior. The millennial generation, who are active users of social media, are increasingly selective in choosing where to exercise, influenced by factors such as facilities, promotions, and word of mouth. This trend can be seen at New Raja Gym in Banda Aceh, which offers modern facilities and  variety of exercise programs to attract millennials to a healthy lifestyle. The objective of this study is examine and analyze the influence of Facilities, Word of Mouth, and Social Media Promotions on the decision to choose place to exercise among millennials at New Raja Gym in Banda Aceh. The sample size for this study was 78 respondents. Research data was collected through questionnaires and documentation studies. Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to determine the effect of independent variables on dependent variables at confidence interval of 95% (α = 0.05). The results of the study show that simultaneously, the variables of Facilities, Word of Mouth, and Social Media Promotion influence the decision to choose place to exercise among Millennials at New Raja Gym in Banda Aceh. Then, partially, Facilities and Word of mouth Social Media Promotion influence the decision to choose place to exercise among Millennials at New Raja Gym in Banda Aceh City. Meanwhile, Social Media Promotion does not influence the decision to choose a place to exercise among Millennials at New Raja Gym in Banda Aceh City.